Downscaled precipitation applied in modelling of mass balance and the evolution of southeast Vatnajökull, Iceland. Issue 228 (2015) - Hannesdóttir, Hrafnhildur; Ađalgeirsdóttir, Guðfinna; Jóhannesson, Tómas; Guđmundsson, Sverrir; Crochet, Philippe; Ágústsson, Hálfdán; Pálsson, Finnur; Magnússon, Eyjólfur; Sigurđsson, Sven Þ.; Björnsson, Helgi
Abstract: Simulations of the post-Little Ice Age evolution of three outlet glaciers of southeast Vatnajökull, Iceland – Skálafellsjökull, Heinabergsjökull and Fláajökull – are presented. A coupled shallow-ice-approximation ice-flow and degree-day mass-balance model is applied that is calibrated with a 14 year record of in situ mass-balance measurements. The measured mass balance cannot be realistically represented by constant horizontal and vertical precipitation gradients. High-resolution (1 km) precipitation fields, derived from downscaled orographic atmospheric circulation models of precipitation, are required to capture the spatial variation of the winter mass balance. The observed ice volume around 1890 (15–30% larger than in 2000) can be simulated with 1°C lower temperatures and a 20% reduction in the annual precipitation, relative to the reference climate period, 1980–2000. The sensitivity of each glacier's annual balance to a change in temperature is −1.51 to −0.97 m w.e. a −1 °C −1 and +0.16 to +0.65 m w.e. a −1 for a 10% increase in precipitation. A steady-state experiment applying a step increase in temperature of 2°C (3°C), and precipitation increase of 10%, results in a >50% (80–90%) decrease in ice volume.